Out of Africa - Mirage Production ([s.l.] Mirage Production, 1985)
Out of Africa is the fascinating true story of Karen Blixen, a strong willed woman who, with her philandering husband (Klaus Maria Brandaver), runs a caffee plantation in Kenya, to her astonishment she soon discovers herself falling in love with the land, its people and the mysterious white hunter, Robert Redfort
VCD
Based on the books 'Out of Africa', 'Shadows of the Grass' and letters from Africa by Isak Dinesen
Keywords: Love--Drama.; Feature films